Access to rehabilitation: patient perceptions of inequalities in access to specialty pain rehabilitation from a gender and intersectional perspective. Issue 1 (1st December 2016) - Wiklund, Maria; Fjellman-Wiklund, Anncristine; Stålnacke, Britt-Marie; Hammarström, Anne; Lehti, Arja
Abstract : Background: Long-term musculoskeletal pain is common, particularly among women. Pain conditions are a concern in primary health care, and people with severe and complex pain are referred to specialty health care. There is gender bias in access, counselling, assessment, and treatment of long-term pain. Objective: This study explores patient accounts and perceptions about important (social) factors for accessing specialised pain rehabilitation from gender and intersectional equality perspectives. We aimed to identify potential biases and inequalities in accessing rehabilitation resources at a specialised rehabilitation clinic. Design: Individual semi-structured interviews were conducted with 10 adults after an assessment or completion of a specialised rehabilitation programme in northern Sweden. Qualitative content analysis was used to explore patients' perceptions of important factors for accessing rehabilitation. Results: One main theme was formulated as Access to rehab – not a given . Three categories of perceived inequality were demonstrated: power of gender, power of social status, and power of diagnosis. Participants perceived rehabilitation as a resource that is not equally available, but dependent on factors such as gender, socio-economic status, ability to work, ethnicity, or age, and more subtle aspects of social status and habitus (e.g. appearance, fitness, and weight). The character of diagnosis received (medical versus psychiatric or social) was also noted. Conclusions: It is crucial that professionals are aware of how potential inequalities related to gender, social status, and diagnosis, and their intersections, can be created, perceived, and have influence on the processes of assessment and treatment. Reduction of social determinants of health and biases remain important within global, national, and local contexts.